2016
DOI: 10.1038/nm.4046
|View full text |Cite
|
Sign up to set email alerts
|

Transient inhibition of ROR-γt therapeutically limits intestinal inflammation by reducing TH17 cells and preserving group 3 innate lymphoid cells

Abstract: RAR-related orphan receptor γt (ROR-γt) directs differentiation of pro-inflammatory T helper 17 (TH17) cells and is a potential therapeutic target in chronic autoimmune and inflammatory diseases1–3. However, ROR-γt-dependent group 3 innate lymphoid cells (ILC3s) provide essential immunity and tissue protection in the intestine4–11, suggesting that targeting ROR-γt could also result in impaired host defense to infection or enhanced tissue damage. Here, we demonstrate that transient chemical inhibition of ROR-γt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
171
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(184 citation statements)
references
References 46 publications
13
171
0
Order By: Relevance
“…Transcription factors regulating cytokine gene expression are potential future drug targets in IBD 119,120 . Theoretically, targeting such regu latory proteins might enable suppression of the produc tion of several proinflammatory cytokines at the same time.…”
Section: T Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription factors regulating cytokine gene expression are potential future drug targets in IBD 119,120 . Theoretically, targeting such regu latory proteins might enable suppression of the produc tion of several proinflammatory cytokines at the same time.…”
Section: T Cellmentioning
confidence: 99%
“…Potential strategies for targeting include siRNA, DNAzymes and chemical inhibitors. A study published in 2016 used a chemical inhibitor of RORγt, a master transcription factor in T H 17 cells, for successful ther apy of experimental T cell dependent colitis in mice 120 . Furthermore, genetic RORγ deficiency of T cells pre vented T cell transfer of colitis in RAG knockout mice 84 .…”
Section: T Cellmentioning
confidence: 99%
“…Hence, cpd 1 appears not to generally affect intestinal integrity despite potential changes in IL-17 production in the gut. Recently, it has been shown that pharmacological inhibition of RORC is therapeutically efficacious in a mouse model of intestinal inflammation and selectively reduces cytokine production from Th17 cells, but it preserves innate lymphoid cells in a mouse intestinal infection model (25). Genetic Rorc deficiency in mice causes strong perturbations of the immune system, as well as development of metastasizing thymic T cell lymphomas (1,10,11,12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Among Th cell subsets, Th17 cells have been implicated in the mediation of tissue destruction in a wide range of inflammatory diseases including inflammatory bowel disease (IBD) (7)(8)(9). In support of the functional relevance of Th17 cell biology in intestinal inflammation, specific targeting of the Th17 differentiation-regulating transcription factor RORγt limited experimental colitis (7,10). However, whether alloreactive Th17 cells promote GVHD-associated intestinal inflammation is a matter of controversy, since independent studies yielded partially contradictory results (7)(8)(9)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%